Maintenance therapy and need for cessation studies in multiple myeloma: Focus on the future. Issue 1 (March 2020) - Diamond, Benjamin; Maclachlan, Kylee; Chung, David J.; Lesokhin, Alexander M.; Ola Landgren, C.
Abstract: With ten years of follow-up since the advent of the modern paradigm of combination induction therapy, consolidative autologous stem-cell transplant, and lenalidomide maintenance, median survival for multiple myeloma has increased to almost 50% at 10 years. Given this outlook, the overarching goal of maintenance therapy is to spare patients from the toxicities of aggressive or otherwise intrusive therapies while ideally extending survival or, at the least, extending progression-free survival or time until next treatment. This review will focus on the current landscape of maintenance therapies for multiple myeloma. The historical context and evidence for choice of agent, duration of treatment, and current strategies and ongoing trials will be discussed – as well as a focus on unmet needs. The case for studies investigating cessation of therapy and risk and response-adapted approaches will be underscored given that the current paradigm likely results in overtreatment for some patients.